TROP2, androgen receptor, and PD‐L1 status in histological subtypes of high‐grade metaplastic breast carcinomas. Issue 5 (9th January 2023) - Chartier, Suzanne; Brochard, Camille; Martinat, Charlotte; Coussy, Florence; Feron, Jean‐Guillaume; Kirova, Youlia; Cottu, Paul; Marchiò, Caterina; Vincent‐Salomon, Anne
Abstract : Aims: High‐grade metaplastic breast carcinoma (HG‐MBC) is a rare subtype of invasive breast carcinoma, mostly triple‐negative. Metaplastic carcinomas are less responsive to neoadjuvant chemotherapy and are associated with a worse outcome than invasive carcinomas of no special type. Methods: Clinicopathological characteristics and immunophenotype were retrospectively assessed in a series of 65 patients diagnosed with HG‐MBC between 2005 and 2017 at the Curie Institute (antibody panel: oestrogen receptor [ER], progesterone receptor [PR], androgen receptor [AR], human epidermal growth factor receptor 2 [HER2], programmed death ligand‐1 [PD‐L1], and trophoblast cell surface antigen 2 [TROP2]). Results: The median age at diagnosis was 59.5 years. Six (9%) patients had metastatic disease at diagnosis. Among the nonmetastatic patients receiving neoadjuvant therapy, 26% (5/19) achieved pathological complete response. Most tumours were pT1/pT2 (77%) and 12% were pN+. Histological subtypes (mixed, squamous, mesenchymal, and spindle cell) were 40%, 35.5%, 15.5%, and 9%, respectively. Tumour‐infiltrating lymphocytes were low or moderate except when squamous differentiation was present. Most tumours were triple‐negative (92%). AR and TROP2 were positive in 34% and 85% of the cases, respectively. PD‐L1 was positive in tumour cells in 18% (cutoff: 1% of positive tumour cells) of the cases and in tumour‐infiltrating immune cells in 40% (cutoff: 1% of tumour area) of the cases. Notably, spindle cell and mesenchymal metaplastic breast carcinomas were mostly PDL1‐negative. Lastly, 21 (32.3%) cases were HER2‐low, all being HER2 1+, with no HER2 2+. Conclusion: Metaplastic breast carcinoma could benefit from tailored therapeutic strategies adapted to the phenotypic specificities of histological subtypes. Abstract : Representative immunostaining examples of androgen receptor (A & B ), trophoblast cell surface antigen 2 (C & D ), and programmed death ligand‐1 (E & F ) expression in metaplastic breast carcinoma. Focal nuclear expression of androgen receptor in mesenchymal (A) and squamous (B) component of high‐grade metaplastic breast carcinoma (HG‐MBC). (C) Example of trophoblast cell surface antigen 2 (Trop2) cytoplasmic expression in a squamous component of HG‐MBC. (D) Strong, diffuse, and membranous staining of Trop2, in a squamous component. (E) Example of programmed death ligant‐1 (PD‐L1) expression in tumour cells: cytoplasmic heterogeneous staining of a squamous component. (F) Example of immune cells staining with PD‐L1‐antibody in a squamous component.